2021
DOI: 10.1029/2020rs007177
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Vertical Correlation Distances: Estimation From ISR Data, Analysis, and Implications For Ionospheric Data Assimilation

Abstract: The construction of the background covariance matrix is an important component of ionospheric data assimilation algorithms, such as Ionospheric Data Assimilation Four‐Dimensional (IDA4D). It is a matrix that describes the correlations between all the grid points in the model domain and determines the transition from the data‐driven to model‐driven regions. The vertical component of this matrix also controls the shape of the assimilated electron density profile. To construct the background covariance matrix, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…For retrieval of the electron density from VH data, only the vertical direction is considered, making it a 1‐D problem. Typically, to model the vertical component of the covariance matrix an assumption is used that the vertical correlations are represented by a Gaussian (Aa et al., 2015, 2016; Bust & Crowley, 2007; Bust & Datta‐Barua, 2014; Bust et al., 2001, 2004; Coker et al., 2001; Forsythe, Azeem, & Crowley, 2020; Forsythe et al., 2021; Yue et al., 2007, 2011). The construction of the error covariance matrix P can be separated into the construction of two matrices: the model variance matrix V and the vertical correlation matrix trueCver.…”
Section: Data Assimilationmentioning
confidence: 99%
See 3 more Smart Citations
“…For retrieval of the electron density from VH data, only the vertical direction is considered, making it a 1‐D problem. Typically, to model the vertical component of the covariance matrix an assumption is used that the vertical correlations are represented by a Gaussian (Aa et al., 2015, 2016; Bust & Crowley, 2007; Bust & Datta‐Barua, 2014; Bust et al., 2001, 2004; Coker et al., 2001; Forsythe, Azeem, & Crowley, 2020; Forsythe et al., 2021; Yue et al., 2007, 2011). The construction of the error covariance matrix P can be separated into the construction of two matrices: the model variance matrix V and the vertical correlation matrix trueCver.…”
Section: Data Assimilationmentioning
confidence: 99%
“…Each element of this matrix can be modeled as trueCijver={casesleftexpfalse(zizjfalse)2false(L1false(zi,λifalse)false)2,leftifzi<zjleftexpfalse(zizjfalse)2false(L2false(zi,λifalse)false)2,leftifzi>zj,left1,leftifzi=zj where z is the height, λ is the magnetic latitude, L 1 and L 2 are functions of altitude and magnetic latitude, and subscripts i and j refer to the pairs of grid points. The vertical correlation lengths L 1 and L 2 depend on the geomagnetic latitude and height (Forsythe et al., 2021) and can be found at the data repository cited in (Forsythe et al., 2021). In the current study, the correlation lengths L 1 and L 2 were reduced by half because this showed more stable performance of the assimilation algorithm.…”
Section: Data Assimilationmentioning
confidence: 99%
See 2 more Smart Citations
“…Many investigations have explored the spatial correlation distances of the ionosphere. For example, horizontal correlation distances have been studied using TEC data (Forsythe, Azeem, & Crowley, 2020; Gail et al, 1993; Klobuchar et al, 1995; Shim et al, 2008; Yue et al, 2007), and vertical correlation distances have been investigated using Incoherent Scatter Radar (ISR) data (Forsythe, Azeem, Crowley, & Themens, 2020; Yue et al, 2007). To the best of our knowledge, no previous investigations have examined in detail the temporal ionospheric correlation or the relaxation parameter.…”
Section: Introductionmentioning
confidence: 99%